Decentralized Bargaining : Its Problems and Direction in Ontario and the Western Provinces - Muir, J. (Relations industrielles / Industrial Relations, 1971)
This paper is directed to the bargaining structure issue and examines the problems and direction of decentralized bargaining in British Columbia, Alberta and Ontario